Mechanisms underlying disruption of oocyte spindle stability by bisphenol compounds. Issue 4 (April 2020) - Yang, Luhan; Baumann, Claudia; De La Fuente, Rabindranth; Viveiros, Maria M
Abstract : Accurate chromosome segregation relies on correct chromosome-microtubule interactions within a stable bipolar spindle apparatus. Thus, exposure to spindle disrupting compounds can impair meiotic division and genomic stability in oocytes. The endocrine disrupting activity of bisphenols such as bisphenol A (BPA) is well recognized, yet their damaging effects on spindle microtubules (MTs) is poorly understood. Here, we tested the effect(s) of acute exposure to BPA and bisphenol F (BPF) on assembled spindle stability in ovulated oocytes. Brief (4 h) exposure to increasing concentrations (5, 25, and 50 µg/mL) of BPA or BPF disrupted spindle organization in a dose-dependent manner, resulting in significantly shorter spindles with highly unfocused poles and fragmented pericentrin. The chromosomes remained congressed in an abnormally elongated metaphase-like configuration, yet normal end-on chromosome-MT attachments were reduced in BPF-treated oocytes. Live-cell imaging revealed a rapid onset of bisphenol-mediated spindle MT disruption that was reversed upon compound removal. Moreover, MT stability and regrowth were impaired in BPA-exposed oocytes, with few cold-stable MTs and formation of multipolar spindles upon MT regrowth. MT-associated kinesin-14 motor protein (HSET/KIFC1) labeling along the spindle was also lower in BPA-treated oocytes. Conversely, cold stable MTs and HSET labeling persisted after BPF exposure. Notably, inhibition of Aurora Kinase A limited bisphenol-mediated spindle pole widening, revealing a potential interaction. These results demonstrate rapid MT disrupting activity by bisphenols, which is highly detrimental to meiotic spindle stability and organization. Moreover, we identify an important link between these defects and altered distribution of key spindle associated factors as well as Aurora Kinase A activity.